KEBIJAKAN REDAKSI DALAM MENENTUKAN BERITA PADA RUBRIK TOTAL SPORT DI SURAT KABAR RIAU POS - Fera Fernanda; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
News presentations on a rubric on the newspaper media is the result of coverage by a journalist. In addition to journalist, for the existence of news or the location of news on a rubric in the newspaper media will not be separated from the interaction editor. In sports coverage packed trough the rubric total sports, editors with teams have full autority in the determination of news, the selection of news topics and publishing. After reporters returned by reporting news acording to coverage in the field, the news will be filtered, peeled and packaged in one term “editorial kitchen” this isi where the editorial team apply the policy in determine the the news. This research aims to determine the role of editors in determining the news on the total rubric sports in Riau Post newspaper, knowing the setting of news on the Arena page and know the process of news coverage on the page Ayo PSPS.This research uses qualitative research type with descriptive approach. Subjects in the study were responsible for Riau Post coverage, Riau Post journalist, and the person responsible for the page chosen by purposive technique. This study uses data collection techniques through interviews, observation, and documantation. To achieve the validity of the data in this study , the authors use extension of participation and triangulation.The results show that first, the person who has authority in determining the news in this total sports rubric is the person responsible for the page. Secondly, the the setting of news arena page is based on the editorial policy or responsible for the page, which is putting forward the regional side, prioriziting high value news. Third, tehe news coverage process on the page Ayo PSPS the same as the coverage of sports news in general, which begins with the process of planning the coverage either based on innitiative and direction . Must observe the chronology of events so that the news produced can packed properly and declared eligible to appear by the responsible pag